Internal conflict and organizational communication on student organizational performance: The mediating role of organizational motivation - Supri Handayani (Enrichment : Journal of Management, 2026)
This study aims to analyze the influence of internal conflict and organizational communication on student organizational performance, with organizational motivation as a mediating at Institute of Technology and Business Indragiri. The study used a quantitative approach with a survey method. Data was collected through questionnaires (google form) from the leaders and members of student organization. This study used analysis technique with path analysis to test the direct and indirect effects between the research variables. The results of the study indicate that internal conflict has a positive effect on student organizational performance. Organizational communication has a positive effect on student organizational performance. In addition, internal conflict and organizational communication has a positive effect on organizational motivation. Organizational motivation significantly influences the student organizational performance and is proven to mediate the influence of internal conflict and organizational communication. These findings indicate that constructive internal conflict and effective organizational communication can increase the organizational motivation of members, which in turn has an impact on improving the overall student organizational performance